Keep Candy in the House - Stephanie Mason (Art/Research International, 2021)
My mother’s love of Tootsie Rolls was the only fact I could grasp after her sudden passing. I wanted to share this and other memories of her through a eulogy that was whimsical, far-ranging, and entertaining, but I struggled to write one. My struggles reminded me of other writing challenges, such as my recent dissertation proposal, although there I was partly guided by my arts-informed research methodology framework. Gradually, I found some of those methodological elements could illuminate parts of eulogy writing: formal concerns, audience, presence and engagement, subjectivity, and meaning-making all resonate with arts-informed research’s commitment to form, audience, creative enquiry, researcher presence, and holistic quality. These connections show arts-informed research affords lifelong learning opportunities apart from academic practice; in this case, arts-informed research is a resource tool for navigating lived experiences of grief and grief writing. Moreover, arts-informed research encourages affective narratives and socially-constructed meanings to produce new understandings, which I realize here by including eulogy excerpts to produce an artistic representation of “research” about my mother (including her undying love of chocolate).